Violencia contra las mujeres y libertad de expresión: tensiones jurídicas - Arroyo Navarrete, Larissa (CIICLA, Universidad de Costa Rica, 2017)
Objectification and sexualization of women in the media and advertising involves the naturalization of violence towards them through humor and other traditions. While there is an international human rights framework which provides special protection for women, this contrasts with the legal protection freedom of expression also receives as a pillar of our democratic systems. In Costa Rica, it is urgent to have legislation that identifies the duties of the Costa Rican government regarding the right to equality and non-discrimination and to live free of violence, as well as the limits of freedom of expression when, through the use of roles and gender stereotypes and the sexualization of women’s bodies in the media and advertising, this freedom has a historical, structural and systematic impact as gender based violence, like in the emblematic case of the radio program Manicomio de la Risa.